Thermophysiological Comfort Assessment of Football Jersey Fabrics used in Hot and Humid Weather - Suraya Ahmad Suhaimi; Wan Syazehan Ruznan; Raja Nurul Jannat Raja Hussain; Mohd Azlin Mohd Nor; Nurul Hidayah Abdul Aziz; Nor Ikhmar Madarsa; Mohd Rozi Ahmad (International Journal of Integrated Engineering, 2025)
Optimizing thermophysiological comfort is crucial for enhancing athletic performances and well-being during intense exercise in hot and humid climates. This study assessed the comfort properties of four commercially available 100% polyester microfibre fabrics used in football jerseys: mini mesh (MM), polar eyelet (PE), eyelet (EY), and interlock (IT). Fabric assessments were conducted to evaluate thermal resistance, water vapour resistance, water vapour permeability, air permeability, and moisture management properties. Among the fabrics, the PE fabric demonstrated to give the most superior thermophysiological properties, with the lowest thermal resistance (0.009 m²K/W), the lowest water vapour resistance (0.44 m²Pa/W), and the highest water vapour permeability (237.7 g/m²/day) and air permeability (2149.2 mm/s). These values are attributed to the fabric’s porous, open-knit structure that enhances heat and moisture dissipation, resulting in improved breathability and wearer comfort. Statistical analysis confirmed significant differences among the fabric structures, reinforcing the influence of fabric design on comfort performance. The findings suggest that, among the fabrics, the PE fabric performs better as sportswear for tropical climates like Malaysia.